Lama menjadi Kader dan Pengetahuan Kader dalam Pencegahan Stunting menggunakan Video Animasi - Titik Sapartinah; Titi Mursiti; Heny Rosiana (Midwifery Care Journal, 2026)
Stunting is a condition of stunted growth in children under five years of age (toddlers) resulting from chronic malnutrition and recurrent infections, particularly during the "First 1,000 Days of Life" period, spanning from the fetal stage until the child is 23 months old. The aim of the research was to analyze knowledge of the cadres in prevention of stunting by animated video compared with buklet in Kendal district. Methods of the study used quasi-experimental with pre test and post test groups. The study was conducted in 2024 in Kendal district used purpossive sampling. The respondents was 18 respondents in animated video groups as intervention group and 17 respondents in Booklet group as control group. The result was education in intervention and control was at junior high school at the most. Therere was effect of animated video intervention in knowledge of the cadres. that there is a statistically significant difference in effectiveness between video animation media and booklet media on the level of respondents' knowledge. With a positive Mean Difference value of 1.967 (and if referred back to the higher average posttest value of the video animation group), it can be concluded that video animation media is significantly more effective in increasing knowledge compared to booklet media. Animated video and Buklet was suggested to be media to educate pregnant women in stunting prevention.